Community-based cardiovascular Risk Factors Intervention Strategies (CORFIS) in managing hypertension: A pragmatic non-randomised controlled trial - Low, W.H.H.; Seet, W.; Ramli, A.S.; Ng, K.K.; Jamaiyah, H.; Dan, S.P.; Teng, C.L.; Lee, V.K.M.; Chua, S.S.; Faridah Aryani, M.Y.; Karupaiah, T.; Chee, W.S.S.; et al. (2013)
BACKGROUND: Hypertension is the number one cardiovascular risk factor in Malaysia. This study aimed to evaluate the effectiveness of a Community-Based Cardiovascular Risk Factors Intervention Strategies (CORFIS) in the management of hypertension in primary care. METHODS: This is a pragmatic, non-randomized controlled trial. Seventy general practitioners (GPs) were selected to provide either CORFIS (44 GPs) or conventional care (26 GPs) for 6 months. A total of 486 hypertensive patients were recruited; 309 were in the intervention and 177 in the control groups. Primary outcome was the proportion of hypertensive patients who achieved target blood pressure (BP) of <140/90mmHg (for those without diabetes mellitus) and <130/80mmHg (with diabetes mellitus). Secondary outcomes include change in the mean/median BP at 6-month as compared to baseline. RESULTS: The proportion of hypertensive patients who achieved target BP at 6-month was significantly higher in the CORFIS arm (69.6) as compared to the control arm (57.6), P=0.008. Amongst those who had uncontrolled BP at baseline, the proportion who achieved target BP at 6-month was also significantly higher in the CORFIS arm (56.6) as compared to the control arm (34.1), p<0.001. There was no difference in the patients who had already achieved BP control at baseline. There were significant reductions in SBP in the CORFIS arm (median -9.0mmHg; -60 to 50) versus control (median -2mmHg; -50 to 48), p=0.003; as well as in DBP (CORFIS arm: median -6.0mmHg; ranged from -53 to 30 versus control arm: median 0.0mmHg; ranged from -42 to 30), p<0.001. CONCLUSIONS: Patients who received CORFIS care demonstrated significant improvements in achieving target BP.